Elderly Health Gallery Training Through Healthy Gymnastics as an Effort to Improve the Quality of Life - Ummul Khair Hasni; Ainun Afifah M. A. Machmud; Nur Fitri Annisa; Firmanto Firmanto (PT. Global Research Collaboration, 2024)
The aging process affects various aspects of life, including health, economic and social. In the elderly, decreased muscle strength and body balance can increase the risk of falls and reduce quality of life. With the projected number of elderly continuing to increase, especially in developing countries like Indonesia, it is important to improve healthy lifestyles as an effort to improve the quality of life of the elderly. This research focuses on the implementation of a healthy exercise program in Taraweang Village, Labakkang District, Pangkajene Regency and South Sulawesi Islands, as part of community service activities. This program involves forming a cadre for the Elderly Health Gallery, providing health education, simple exercise training, and routine exercise activities. The results show an increase in elderly participation in routine exercise, with the number of participants increasing from 26 to 35 people during the implementation period. This healthy exercise has been proven to help improve body organ function, immunity and quality of life for the elderly, as well as providing social and mental benefits. This program is also expected to encourage understanding of the importance of routine health checks and physical activity in the elderly to improve their overall quality of life.